QUANTITATIVE PHASE ANALYSIS OF THE ZrNbMoGe ALLOYS USING NEUTRON DIFFRACTION TECHNIQUES - Parikin Parikin; A. Fajar; A. Insani; A. H. Ismoyo; B. Bandriyana (Center for Science & Technology of Advanced Materials - National Nuclear Energy Agency, 2012)
QUANTITATIVE PHASE ANALYSIS OF THE ZrNbMoGe ALLOYS USING NEUTRON DIFFRACTION TECHNIQUES. Quantitative analysis by neutron diffraction technique can be utilized to measure not only the type of compounds but also the amount of compounds present in a solid or powder system. The technique has been proven for a composition analysis due to offering some advantages particularly for elements with very similar atomic numbers, and for their high penetrating power. A quantitative phase analysis experiment by using neutron diffraction has recently been carried out to determine the amount present of phases in ZrNbMoGe system. The data analysis was obtained by Rietveld refinement method. The result shows that the profiles have a very good fitting (Rwp = 12.62 %, 15.45 % and 16.39 %) with the number of reliable factor among 1.0 and 2.0. The phases of Zr, ZrMo2 , Zr3Ge and ZrGe are identified in the specimens. The ZG1 specimen contains of 94.19 %wt of Zr phase, 2.05 %wt of ZrMo2 phase, 3.15 %wt of Zr3Ge and 0.59 %wt of ZrGe phase. Whereas the ZG2 specimen comprises of: 84.45 %wt of Zr phase, 4.16 %wt of ZrMo2 phase, 10.18 %wt of Zr3Ge and 1.20 %wt of ZrGe phase. The volume fraction of the minor phases on specimens shows an increase as addition in Ge content.